Neuroprotection by upregulation of the major histocompatibility complex class I (MHC I) in SOD1G93A mice - Tomiyama, Ana Laura M. R.; Cartarozzi, Luciana Politti; de Oliveira Coser, Lilian; Chiarotto, Gabriela Bortolança; Oliveira, Alexandre L. R. (Frontiers in Cellular Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that progressively affects motoneurons, causing muscle atrophy and evolving to death. Astrocytes inhibit the expression of MHC-I by neurons, contributing to a degenerative outcome. The present study verified the influence of interferon β (IFN β) treatment, a proinflammatory cytokine that upregulates MHC-I expression, in SOD1G93A transgenic mice. For that, seventy days old presymptomatic female mice were subjected to subcutaneous application of IFN  (250 IU, 1,000 IU, and 10,000 IU) every other day for twenty days. Rotarod motor test, clinical score, and body weight assessment were conducted every third day throughout the treatment period. No significant intergroup variations were observed in such parameters during the pre-symptomatic phase. All mice were then euthanized, and the spinal cords collected for comparative analysis of motoneuron survival, reactive gliosis, synapse coverage, microglia morphology classification, cytokine analysis by flow cytometry, and RT–qPCR quantification of gene transcripts. Additionally, mice underwent Rotarod motor assessment, weight monitoring, and neurological scoring. The results show that IFN β treatment led to an increase in the expression of MHC-I, which, even at the lowest dose (250 IU), resulted in a significant increase in neuronal survival in the ALS presymptomatic period which lasted until the onset of the disease. The treatment also influenced synaptic preservation by decreasing excitatory inputs and upregulating the expression of AMPA receptors by astrocytes. Microglial reactivity quantified by the integrated density of pixels did not decrease with treatment but showed a less activated morphology, coupled with polarization to an M1 profile. Disease progression upregulated gene transcripts for pro- and anti-inflammatory cytokines, and IFN β treatment significantly decreased mRNA expression for IL4. Overall, the present results demonstrate that a low dosage of IFN β shows therapeutic potential by increasing MHC-I expression, resulting in neuroprotection and immunomodulation.